Emulsion stability of clove oil in chitosan and sodium alginate matrix. Issue 1 (1st January 2018) - Purwanti, Nanik; Zehn, Azmi Syahrian; Pusfitasari, Eka Dian; Khalid, Nauman; Febrianto, Erfin Yundra; Mardjan, Sutrisno Suro; Andreas; Kobayashi, Isao
ABSTRACT: Clove oil was emulsified in 1% w/w chitosan (CC emulsions) and 2.5% w/w sodium alginate matrix (CA emulsions) containing Tween 80 as the surfactant. Different homogenization speeds (5, 000, 10, 000, 15, 000 and 20, 000 rpm) were used to produce the emulsions, and the stability of the emulsions during storage (29 days) was determined. The stability of the emulsions containing clove oil prior to the solidification process was assessed when chitosan and sodium alginate were used as encapsulating materials. Different homogenization speeds resulted in polydisperse emulsions with a size of 2–3 μm and 90% of stability after 29 days of storage. Different homogenization speeds did not significantly affect the concentrations of the active compounds contained in the emulsions. However, these concentrations changed significantly after 29 days of storage when sodium alginate was used to make the emulsions and the homogenization speeds were ≥ 10, 000 rpm. High temperature caused by the high viscosity of the solution and high energy dissipation during homogenization suggested that the emulsions composed of sodium alginate were unstable. Chitosan enabled a longer processing time during the clove oil encapsulation process compared to sodium alginate, when emulsification by homogenization was used. The stability of the emulsion of the clove oil-in-chitosan matrix prior to the solidification step was superior.